Novel sandwiched structures in starch/cellulose nanowhiskers (CNWs) composite films - Liu, D.; Dong, Yu; Bhattacharyya, D.; Sui, G. (Elsevier, 2017)
Novel sandwiched structures of cellulose nanowhiskers (CNWs) were found for the first time at the cross section of fractured starch/CNWs composite films. CNWs were obtained by hydrolysing bleached flax yarns through heating in a concentrated sulfuric acid (60 wt. %) aqueous solution at 55 °C for 60 min. Starch and starch/CNWs composite films were prepared by casting starch and mixtures of starch/CNWs homogenous aqueous suspensions, which was followed by drying at atmosphere. The CNWs’ layers are sandwiched within starch matrices in a parallel direction to nanocomposite film surfaces. The layer thickness increases with an increase in the content of CNWs. The discovery of novel sandwiched structures demonstrates that both the interaction and evaporation rate of the solvent can affect the dispersion and thus play important roles in the nanoparticle dispersion. Such nanocomposite films in the presence of self-assembled multi-layer structures may further improve mechanical and gas barrier properties as a promising material candidate for food packaging applications.